Processus gravitaires dans la vallée Tasiapik (Nunavik) : témoins géomorphologiques de la dynamique de versant récente et passée - Veilleux, Samuel (Université Laval, 2019)
This research project was conducted near Umiujaq (Nunavik) to document the main gravitational processes that occur on the slopes of Tasiapik Valley. 18 talus slopes on the southwest and northeast sides of the valley were characterized using topographic, granulometric, morphometric petrographic and vegetation surveys. Results show that talus formation in the valley is an ancient phenomena, due to paraglacial processes, and recent - and still ongoing – periglacial processes. This is evidenced by different development stages among the talus slopes, with fresh and very old debris covering the slopes, as well as contrasting slope topographies. On a shorter and more recent time scale, from August 2017 to July 2018, snow avalanches have proven to be a major process, as observed on the 14,000 photographs obtained using three automatic timelapse cameras installed in the summer of 2017. Snow avalanches were often triggered by a collapsing snow-cornice and were very frequent in the spring of 2018 due to favourable meteorological conditions such as a rapid increase in daily temperatures and abundant rainfall events. Dirty snow-avalanche deposits have shown the great erosive capacity of these snow avalanches, thus their important debris supply toward the talus slopes. In some cases, runout zones were located only a few meters from the road below, thus showing the potential risk for people travelling on the road Ce projet de recherche, mené près d’Umiujaq (Nunavik), a été réalisé afin de documenter les processus gravitaires dominants qui se manifestent sur les versants escarpés de la vallée Tasiapik. Des relevés topographiques, granulométriques, morphométriques, pétrographiques et de végétation ont permis de caractériser 18 talus d’éboulis situés sur les versants sud-ouest et nord-est. Les résultats obtenus ont permis d’établir que l’éboulisation importante sur les versants de la vallée est un phénomène à la fois ancien, engendré par des processus paraglaciaires, et récent, résultat de processus périglaciaires toujours ...